Enhancing Quality Fruit Composition in Red Currant Cultivars by Foliar Calcium Application across Preharvest and Postharvest Stages - Olga Panfilova; Ibrahim Kahramanoğlu; Gabrijel Ondrasek; Nelli Ryago; Larisa Leonteva; Chunpeng (Craig) Wan; Mikhail Tsoy; Volkan Okatan; Olga Golyaeva; Olga Loretts; Viktor Kukhar; Mikhail Karpukhin (Journal of Food Quality)
Foliar calcium (Ca) treatment exhibits strong potential for enhancing yield and quality in some fruit crops. This study aimed to assess the impact of foliar application of Ca-organomineral (Ca-OM) suspension on total soluble solids (TSS) and Ca dynamics in leaves and berries across five red currant cultivars during the vegetation and storage. A randomized block design with two treatments: (1) Control (without Ca-OM treatment) and (2) foliar Ca-OM treatment, with three repetitions, was applied on five different red currant cultivars. Although foliar Ca-OM treatments did not impact Ca or TSS in leaves, they positively influenced Ca and TSS in fruits, displaying significant variability among cultivars. In addition, Ca-OM treatment increased berry density, reduced abscission, and inhibited the development of diseases, extending storage periods for “Lvovyanka,” “Vika,” and “Gazel” cultivars by three to seven days compared to the Ca-OM untreated control. Ca-OM treatment in the early stages of the ontogenesis of currants provided a high percentage of Ca intake in berries. At the stage of complete maturation, the Ca content in berries decreased and depended on the ripening period of the cultivars. Before harvesting, Ca-OM increased the strength of berries (Fc) and reduced the shedding of berries in the clusters (Fs). At the vegetation stage, Ca-OM increased TSS in berries, and the content of TSS depended on the genotype and weather conditions. The Ca-OM treatment and low temperatures contributed to preserving berry density, reducing the shedding of berries and PLW, and restraining the development of diseases during storage. In addition, the high content of TSS and Ca in berries against the background of a slow rate of decrease in berry density in the Ca-OM variants ensured an extension of the shelf life of “Lvovyanka,” “Vika,” and “Gazel” by three to seven days compared to the control untreated with Ca-OM. Clustering analyses identified these cultivars as similar in terms of TSS and calcium content in fruits, emphasizing their common traits. The study underscores the potential of foliar Ca treatment to enhance berry quality during growth and storage, significantly improve storage duration, and fortify resistance against adverse factors, presenting promising opportunities for elevating yield and quality in specific red currant cultivars.